The Efficacy and Safety of Ultrasound-Guided, Bi-Level, Erector Spinae Plane Block With Different Doses of Dexmedetomidine for Patients Undergoing Video-Assisted Thoracic Surgery: A Randomized Controlled Trial - Gao, Xiujuan; Zhao, Tonghang; Xu, Guangjun; Ren, Chunguang; Liu, Guoying; Du, Ke (Frontiers in Medicine, 2021)
Background: The anesthetic characteristics of ultrasound-guided bi-level erector spinae plane block (ESPB) plus dexmedetomidine (Dex) remain unclear. We compared the efficacy and safety of ultrasound-guided bi-level ESPB plus different doses of Dex in patients undergoing video-assisted thoracic surgery (VATS). Methods: 108 patients undergoing VATS were randomized into three groups. The primary outcome was the pain both at rest and with coughing during 72 h after surgery. Secondary outcomes included Prince Henry Hospital Pain Score; consumption of sufentanil; anesthetized dermatomal distribution; recovery time; number of presses of patient controlled intravenous analgesia (PCIA) pump; number of patients needing rescue analgesia; time to first rescue analgesic; total dose of rescue analgesic; satisfaction scores of patients and surgeon; time of feeding, ambulation, exhaust and removal of chest tubes; adverse effects. Additionally, the prevalence of chronic pain and quality of recovery were assessed at 3 months after surgery. Results: VAS both at rest and with coughing and the Prince Henry pain score were significantly lower in both the RD1 and RD2 groups than in the R group during the first 24 h after surgery (P<0.05). Both VAS with coughing and the Prince Henry pain score were significantly lower in the RD2 group than in the RD1 group during 8–24 h after surgery (P<0.05). Requirement for sufentanil during the 8–72 h after surgery was significantly lower in the RD2 group than in the RD1 group (P<0.05). Less rescue medication and total press times of PCA were used in the RD2 group within 72 h postoperatively (P<0.05). Time to first dose of rescue ketorolac was significantly longer in the RD2 group (P<0.05). Further, anal exhaust, removal of chest tubes, and ambulation were significantly shorter in the RD2 group than in the R and RD1 groups (P<0.05). The incidence of tachycardia, postoperative nausea and vomiting, and chronic pain was significantly reduced in the RD2 group, while the QoR-40 score was significantly higher in the RD2 group (P<0.05). Conclusions: Compared with the other two groups, preoperative bi-level, single-injection ESPB plus 1 µg/kg Dex provided superior pain relief and long-term postoperative recovery for patients undergoing VATS, while adverse effects reduced.